Procalcitonin levels in maternal serum and cord blood as marker for diagnosis of early onset neonatal sepsis - Puja Yadav; Kavita Agarwal; Anita Rani; Rupali Dewan; Harish Chellani (Elsevier, 2023)
Objectives: To assess the diagnostic accuracy of Procalcitonin in maternal serum and umbilical cord blood samples to predict Early onset neonatal sepsis (EONS). Study Design: It was a Prospective analytical cohort study. Pregnant women ≥ 34 weeks gestation in active labour, with risk factors for EONS were included in the study. Maternal blood samples at recruitment and umbilical cord blood samples after delivery were taken for Total leucocyte count (TLC), high sensitivity C-Reactive Protein (hs-CRP) and Procalcitonin. Newborns were classified into non-infected, suspected and proven infection. Sensitivity, specificity and diagnostic accuracy of maternal and cord blood procalcitonin, TLC and hs-CRP were calculated. Results: A total of 200 women were recruited. Maternal procalcitonin had a superior diagnostic accuracy of 99% compared to maternal TLC and maternal hs-CRP. Also, cord blood procalcitonin had a diagnostic accuracy of 95%. Conclusion: Procalcitonin in both maternal as well as cord blood is a promising biomarker to detect EONS with high diagnostic accuracy.